Resiliensi Diri Mahasiswa Semester Akhir Dalam Mengurangi Quarter Life Crisis - Lukmanul Hakim; Fathur Rachman Nufaily; Irsyadunnas (CV. ITTC INDONESIA, 2025)
This study aims to explore the self-resilience strategies developed by final semester students in dealing with academic pressure and quarter life crisis. The main focus of this research is to understand how resilience can help reduce the level of anxiety and uncertainty experienced by students during the transition to the professional world. The method used in this study is a qualitative approach with a phenomenological design, which focuses on the personal experiences of individuals. Data were collected through in-depth interviews with three final semester master's students at UIN Sunan Kalijaga Yogyakarta. The results showed that the three students experienced significant pressure related to the completion of the final project, parents' expectations to graduate soon, and confusion about the future, especially in the aspects of work and marriage. Each respondent showed different resilience strategies, such as completing tasks little by little, doing tasks casually, and managing time even though they had to stay up late. Social support from friends and family, as well as mental health management through leisure and spiritual activities, were found to play a role in reducing stress. This study emphasizes the importance of social support, mental health management, and self-development as key factors in improving students' resilience in facing academic challenges and future uncertainties.